2006
DOI: 10.1016/j.joca.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Falls risk is associated with pain and dysfunction but not radiographic osteoarthritis in older adults: Tasmanian Older Adult Cohort study

Abstract: Self-reported functional ability and pain, and to a lesser extent, stiffness (but not knee and hip ROA), have a modest but independent association with physiological predictors of falls risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
20

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 24 publications
6
82
0
20
Order By: Relevance
“…Another relevant aspect is the association of the presence of pain with the occurrence of stiffness and alterations in functional activities, especially those related to knee flexion. 5,13,17 Leveille et al 17 demonstrated that in elderly individuals with OA the greatest difficulty in the performance of daily functions was related to muscle weakness developed in avoiding the execution of tasks that produced pain, such as climbing stairs or walking for a longer distance. Therefore, pain is an important and common clinical symptom in patients with OA, and can constitute a limiting factor of functional ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant aspect is the association of the presence of pain with the occurrence of stiffness and alterations in functional activities, especially those related to knee flexion. 5,13,17 Leveille et al 17 demonstrated that in elderly individuals with OA the greatest difficulty in the performance of daily functions was related to muscle weakness developed in avoiding the execution of tasks that produced pain, such as climbing stairs or walking for a longer distance. Therefore, pain is an important and common clinical symptom in patients with OA, and can constitute a limiting factor of functional ability.…”
Section: Discussionmentioning
confidence: 99%
“…2 Individuals with knee OA have greater difficulty in performing functional activities, particularly those that involve mobility and transfers when compared with healthy individuals. 4 Functional decline, increased risk of falls and presence of pain are, in many studies, related to the muscle weakness caused by OA, 4,5 especially weakness of the quadriceps and hamstring muscles. 6 Individuals with knee OA present reduction of strength in the muscles of this joint, which might or might not be associated with muscle atrophy, pain and edema.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 21 articles fit the search criteria and were included in the review. 6,7,[9][10][11][12][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although all 21 studies included adults with OA or joint pain (including hip and knee), only 14 were specific to either hip or knee OA. 10,11,12,16,19,[20][21][22][23][25][26][27][28][29] We found few studies that addressed the relationship between personal and environmental contextual factors and fall risk spe- Adapted from the Summary of the updated American Geriatrics Society/British Geriatrics Society clinical practice guideline for prevention of falls in older persons.…”
Section: Methodsmentioning
confidence: 99%
“…16 A second study found a threefold increase in fall risk, as measured by the Physiologic Profile Assessment (PPA), in women who scored higher in function and pain disability (scored b50 on the Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC]) related to their OA. 24 Not all studies produced evidence of site-specific arthritis-related fall risk. The presence of any arthritis or joint pain was shown to be a risk factor for falls.…”
Section: Fall and Fracture Riskmentioning
confidence: 99%
See 1 more Smart Citation